2007
DOI: 10.1007/s10549-007-9646-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional sodium iodide symporter expression in breast cancer xenografts in vivo after systemic treatment with retinoic acid and dexamethasone

Abstract: Treatment with Dex in the presence of atRA is able to induce significant amounts of iodide accumulation in breast cancer xenotransplants in vivo due to stimulation of functional NIS protein expression, which opens exciting perspectives for a possible diagnostic and therapeutic role of radioiodine in the treatment of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 46 publications
3
28
0
Order By: Relevance
“…In breast cancer cells, many authors reported that retinoic acid is a powerful enhancer of NIS expression especially in association with corticosteroids [12][13][14]. Furthermore, in one report it was also observed that retinoic acid and dexamethasone treatment determined a significant 131 I-induced cytotoxicity in breast cancer cells [15].…”
Section: Introductionmentioning
confidence: 98%
“…In breast cancer cells, many authors reported that retinoic acid is a powerful enhancer of NIS expression especially in association with corticosteroids [12][13][14]. Furthermore, in one report it was also observed that retinoic acid and dexamethasone treatment determined a significant 131 I-induced cytotoxicity in breast cancer cells [15].…”
Section: Introductionmentioning
confidence: 98%
“…Administration of dexamethasone (Dex), and carbamazepine (CBZ) together with tRA increased both iodide uptake by NIS, and NIS mRNA expression even more. In response to Dex and CBZ administration, tRA induced I -uptake via NIS have increased about 12 fold in xenograft tumours in experimental animals, clearly indicating that the combination of an RAR isoform selective ligand and Dex and Cbz has a potential to provide a more effective induction of NIS, and it provides an important improvement for the effective use of symporter in theraputic/diagnostic medical approaches (Kogai et al, 2005;Willhauck et al, 2008;.…”
Section: Modulation Of Nis Expression In Breast Cancer Cell Models Anmentioning
confidence: 99%
“…Moreover, we were able to confirm these results in vivo in MCF-7 xenotransplants, which accumulated approx. 3-5% of the injected dose 123 I per gram tumor (% ID/g) after systemic atRA and Dex treatment as shown by gamma camera imaging [15]. However, although a significant iodide uptake activity was induced by atRA and Dex in vivo an additional stimulation of NIS expression is desirable to enhance sensitivity and efficacy of diagnostic and therapeutic application of radioiodine in breast cancer.…”
Section: Mcf-7 Cells In Vitromentioning
confidence: 99%
“…In more recent studies, we and others have demonstrated that dexamethasone (Dex) is able to significantly enhance atRA-induced NIS expression and iodide accumulation in MCF-7 cells in vitro and in vivo [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%